Precise and Sensitive Ambient Temperature Based Analytical Colorimetric Method for Pregabalin - Memoona Rashid; Talib Hussain; Muhammad Sarfraz; Mosab Arafat; Amjad Hussain; Nasir Abbas; Nadeem Irfan Bukhari (Universidade de São Paulo, 2023)
Abstract Pregabalin, a GABA analogue is used to treat epilepsy and neuropathic pain. The drug poses problems in analytical quantification when estimated at a shorter UV wavelength. The expensive and non-repetitive reported analytical methods necessitate the utility and development of an accurate, precise, repetitive, simple and highly sensitive colorimetric method for pregabalin in solution as well as sustained release mini matrices. Pregabalin (having primary amino group) was derivatized at alkaline pH of mixture with optimized ninhydrin solution at ambient temperature (25oC). The ninhydrin-pregabalin derivatized complex (Ruhemann's Purple) was analyzed for drug concentration at absorption maximum (λmax) of 570nm. The linearity was observed in the concentration range of 5-150 µg/mL with coefficient of correlation, 0.998. The developed analytical method was validated according to ICH guidelines and proved to be highly sensitive (LOD 0.917µg/mL, LOQ 3.055µg/mL), with good inter-day as well as intra-day accuracy and precision as 4.65% and 3.75%, respectively. The proposed method was proved to be a simple, sensitive, precise and accurate for the estimation of the minute concentrations of pregabalin in pure form and the developed formulations. Results verified that the proposed method could determine pregabalin at the ambient temperature without requiring high temperatures used in the existing methods. It was concluded that developed method was easier and more suitable for analysis of pregabalin in quality control of commercial preparations.